Single-nucleus neuronal transcriptional profiling of male C. elegans uncovers regulators of sex-specific and sex-shared behaviors - Katherine S. Morillo; Jonathan St. Ange; Yifei Weng; Rachel Kaletsky; Coleen T. Murphy (Cell Reports)
Summary: Sexual differentiation of the nervous system drives profound neurobiological and behavioral differences between the sexes across various organisms, including Caenorhabditis elegans. Using single-nucleus RNA sequencing, we profiled and compared adult male and hermaphrodite C. elegans neurons, generating an atlas of adult male-specific and sex-shared neurons. We expanded the molecular map of male-specific neurons and identified highly dimorphic expression of G protein-coupled receptors (GPCRs), neuropeptides, and ion channels. Our data demonstrate sex-shared neurons exhibit substantial heterogeneity between the sexes, while sex-specific neurons repurpose conserved molecular pathways to regulate dimorphic behaviors. We show that the PHD neurons display remarkable similarity to sex-shared AWA neurons, suggesting partial repurposing of conserved pathways, and that they and the GPCR SRT-18 may play a role in pheromone sensing. We further demonstrate that the ubiquitously expressed MAPK phosphatase vhp-1 regulates both sex-specific and sex-shared behaviors. Our data provide a rich resource for discovering sex-specific transcriptomic differences and the molecular basis of sex-specific behaviors.